Penerapan Model Pembelajaran Kooperatif Numbered Heads Together Terhadap Hasil Belajar Pada Mata Pelajaran Geografi - Cindy Sofia Dodopo; Grystin Djein Sumilat; Muhamad Isa Ramadhan (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2022)
This study aims to determine the effect of applying numbered head together on student learning outcomes in Geography subjects. The study used a pseudo-experimental method of nonequeivalent control group design with pretest posttest control group design totaling 15 experimental class students and 15 control class people. The results showed that there was a difference in the average pretest learning outcomes with the posttest of North Halmahera geography subjects taught using the Numbered Heads Together (NHT) learning model with a mean value of -9,467 and a t value of -5,152. Learning activities using the NHT learning model, have an influence on learning activities shown from student learning activities in class and improvement of student learning outcomes in geography subjects in class XI SMA N 5 North Halmahera.